Effects of the border closure Benin-Nigeria on the marketing of Clarias gariepinus - GOUNOU SABI, Yarou; BABADANKPODJI, Pascaline; Houndonougbo, Kouadio Pierre; MITCHIKPE, COMLAN EVARISTE SIMON; MAMA, ADI; CHIKOU, ANTOINE (My University, 2022)
Abstract The Clarias is consumed in Africa and Benin. Despite its important role in food, its sector is subject to many constraints, including marketing in Nigeria. The objective of this study is to assess the marketing of smoked Clarias in southern Benin in the face of the Nigerian border closure. It is made in the Oueme department. Individual surveys based on structured questionnaires were conducted with 30 fish farmers and 45 processors. From the results obtained, three Nigerian markets are known for the sale of smoked Clarias, of which Badagri is the main destination. The actors in this activity are mostly adults with an average experience over 20 years. Fish farming is mainly the prerogative of men (83.33%) while processing and marketing are the only privilege of women (100%). The closure of the Nigerian border has led to a decrease in the annual fish production of the respondents from 8,960 kg to 7,491.96 kg as well as a decrease in the quantity of smoked fish from 6,249.24 kg to 2,319.96 kg after the border closure. The study shows a decline in the level of income of fish farmers and commercial processors, especially in the achievement of food security in their households. The marketing of smoked fish in Nigeria appears to be a profitable activity for processors.
Keywords: Smoked fish; marketing; border; department; Ouémé